Analisa Metode MGR Untuk Mendeteksi Keaslian Citra Digital - Zay, Rani Aflisa; Mesran, Mesran (TIN: Terapan Informatika Nusantara, 2022)
Digital image processing is an important part that underlies various real applications, such as pattern recognition, remote sensing via satellite or aircraft, and machine vision. In pattern recognition, digital image processing plays a role in separating objects from the background automatically. Almost all applications of information technology use cryptography as a tool to ensure the security and confidentiality of data or information. Because of this, cryptography has become a rapidly growing science and in a short time many new algorithms have emerged which are considered superior to their predecessor algorithms. To see the authenticity of digital images we use the MGR algorithm. MGR hash function based on its design security. Protected against multicollision attacks, fixed point attacks, extension attack lengths and herd attacks and provides better efficiency (three times faster) than GOST-R. AES such as block ciphers have been used in compression design. The MGR function due to AES is one of the most efficient and cipher-secure blocks and has been evaluated for more than 12 years